Fighting Cheating in P2P-based MMVEs with Disjoint Path Routing - Schuster, Sebastian; Wacker, Arno; Weis, Torben (Electronic Communications of the EASST, 2009)
In a P2P-based Massively Multiuser Virtual Environment (MMVE) wherenodes cannot be trusted, replicating data on multiple nodes is a possibility to increasethe reliability to obtain correct data. Current structured P2P networks mostlyplace replicas in such a way that queries for the replicas travel along similar paths.A malicious node in the common part of all paths can nullify the security gain ofreplicated data. We therefore propose to combine radix-based prefix routing with asymmetric replication scheme to gain disjoint paths to each of the replicas.